ANONYMOUS BIRTH VERSUS CHILD’S RIGHT TO IDENTITY - Mladenović, Tamara (Pravni zapisi, 2021)
The right to identity of the child, internationally recognized by the UN Convention on the Rights of the Child, is one of the most important in the corpus of child rights. Its structure is complex since it includes several narrower rights. Nevertheless, the situations where it comes to restriction of the right to identity are not negligible. One of them is the right to anonymous birth, the possibility acknowledged by legislators in a certain number of European countries. Conflicting interests between a mother and a child are inevitable consequence of the anonymous birth.The aim of this article is to compare the right to identity of a child and the mother’s right to anonymous birth as insurmountable barrier in determining biological origin. Special attention is paid to the possibility of establishing an adequate balance between their interests, by comparing the importance that national legal system offers to each of them, with appropriate arguments, several different models of motherhood regulations are presented and can be found in European legislations. The analysis also includes the stances of international bodies, especially the European Court of Human Rights.
Keywords: anonymous birth; child rights; right to identity; European Court of Human Rights